Penggunaan Serat Serabut Kelapa Sebagai Bahan Tambah Campuran AC-BC - Aldi Randa Linggi; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2022)
Problems with the quality of asphalt mixtures and large cavities are things that need attention, so further research is carried out by adding coconut fiber added ingredients to the AC-BC mixture, using coconut fiber as an added ingredient in the Asphalt Concrete – Binder Course mixture is expected to improve the quality of the mixture. , because the function of the coconut fiber mixed into the asphalt mixture can improve the quality of the bond between the aggregates and the asphalt so that the performance of the mixture, especially the stability, becomes stronger. The purpose of this study was to test the use of coconut fiber as an additive in the mixture of Asphalt Concrete – Binder Course. The method used is to design variations in coconut fiber fiber content then manufacture mixed Asphalt Concrete – Binder Course specimens and carry out Conventional Marshall tests. The results of Marshall Conventional research obtained a mixture of Asphalt Concrete - Binder Course with coconut fiber content of 0%, 1%, 2%, 3%, 4%, with an asphalt content of 5% fulfilling the 2018 General Highways Specifications. The addition of coconut fiber can improving the performance of the Laston AC-BC mix, causing the voids in the mixture to become smaller and resulting in a strong and stable mix that can withstand traffic loads.